TELAAH POTENSI KAMPUNG SEBAGAI DASAR PERANCANGAN PUSAT KEBUDAYAAN KAMPUNG PANDEYAN - Arti Setyawati; Endah Tisnawati (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2018)
Title: The Study of Kampung’s Strenght as the Basis for Cultural Center Design at Kampung Pandeyan Yogyakarta is a province with various privileges. Yogyakarta has a lot of history both physical history and non-physical history. Many people know Yogyakarta as a cultural city and student city. Cultural diversity in Yogyakarta is one of the tourist attractions. Travelers not only visit tourist attractions and historical heritage buildings but also are interested in following a cultural atmosphere that is not found elsewhere and is different from the daily lives of tourists. The increasing interest of tourists in knowing the culture in the village is not matched by accommodating facilities. There is still a lack of space for people and artists to appreciating art and culture while educating citizens of the community, so there needs to be a cultural center that serves to appreciate works of art and culture. Pandeyan village has now developed into a village that has begun to be known for its diversity of artistic and cultural potential. An overview of the diverse potential of the village is the basis of design. This scientific paper will discuss the various potentials of the village which are used as the basis for planning a cultural center in Pandeyan Village. The village's cultural center itself is a discourse that wants to be reviewed as a specific function that differs from the center of culture in general. The problem that will be described is how is the design of the Pandeyan village cultural center based on the potential of the village? The design results of this design are designing the cultural center of Pandeyan Village as a facility for the surrounding community in preserving existing art and cultural attractions. The concept is expected to be applied to the form and order of mass composition, the relationship of spaces (both inner and outer space), and the application of ornaments to the elements of inner and outer space.